Halal Awareness: Insights into Gen Z's Perceptions in Indonesia - Hendryadi, Hendryadi (LPMP Imperium, 2024)
This study aims to assess the level of halal awareness among Gen Z in Indonesia and determine if there were any differences in awareness between men and women. The research involved 450 Muslim respondents aged 19 to 25 (Female 54.4 percent), who participated through self-administered questionnaires and convenience sampling. The results indicated a high level of awareness regarding halal food products, with an average mean score of 4.54. Additionally, the comparison between male and female respondents showed no significant differences in their awareness of halal food products. The high level of halal awareness among Gen Z suggests that businesses and marketers should tailor their strategies to this demographic. Companies can leverage this awareness to promote halal products more effectively, emphasizing quality and compliance with halal standards to attract this consumer group. Public interest statements Considering the rising demand for halal food products, food manufacturers and suppliers should explore developing new halal-certified products that meet the preferences and dietary requirements of Generation Z. This may involve creating innovative food choices that align with current trends, such as plant-based or health-focused halal products.